The effects of Piper betle and Alpinia galanga feed additives on growth performance, carcass characteristics and histomorphometry of small intestine in broilers - Mohamed Kamil, Muhammad Ali Imran; Hanif Reduan, Mohd Farhan; Mohd Noor, Mohd Akmal; Abu-bakar, Luqman; Shamsuddin, Shazana Hilda; Mohd Azmi, Amirul Faiz; Mahamud, Siti Nor Azizah; Izamin, Izzati; Hadi Roslan, Muhammad Rasydan; Gilbert, Brenda Sabrina; Abdul Hamid, Fathin Faahimaah (Collage of Veterinary Medicine, University of the Philippines Los Banos, 2024)
Background: The potential in combining Piper betle (betel) and Alpinia galanga (galangal) into a polyherbal formulation in broiler feed is currently unknown despite having numerous individually-established positive effects. The study aims to investigate the effects of the betel and galangal on growth performance, carcass characteristics, and histomorphometry of the small intestine. Methodology: Sixty day-old broiler chicks were randomly grouped into R1 (0.50% betel, 1.50% galangal), R2 (1.00% betel, 1.00% galangal), R3 (1.50% betel, 0.50% galangal) and baseline control group (BC). Weekly growth performance was monitored using FCR. On day 35, carcass characteristics were evaluated after slaughter. Two to three cm of duodenum, jejunum, and ileum were collected for histomorphometry. Statistical one-way ANOVA, Tukey, Kruskal-Wallis and Dunn tests were used. Results: The growth performance showed no significant changes. For carcass characteristics, the dressing percentage of the R1 group significantly increased (p<0.001) at 3.58%, while the R2 group significantly increased (p<0.001) at 3.09%. Additives in R1, R2, and R3 significantly improved (p<0.001) the histomorphometry of duodenum and jejunum, which include villi height, villi width, crypt depth, villi surface area and tunica muscularis thickness. Conclusion: In conclusion, the addition of betel and galangal powder at 2% of broiler feed improves both carcass characteristics and small intestine histomorphometry.